2021
DOI: 10.22603/ssrr.2020-0104
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors and Assessment Using an Endoscopic Scoring System for Postoperative Respiratory Complications after Anterior Cervical Decompression and Fusion Surgery

Abstract: Introduction: Postoperative respiratory complications (PRC) are one of the most serious complications. Potentially life-threatening accidents can occur after an anterior cervical discectomy and fusion (ADF), such as airway obstruction and aspiration pneumonia. Despite numerous studies, preoperative predictive and preventive methodology has yet to be established. As reported in our previous study, the evaluation of preoperative dysphagia using the eating assessment tool (EAT-10) and a flexible endoscopic evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Participants in the oral-intake group were younger than those in the parenteral-intake group, and older age was a risk factor for dysphagia. A previous study reported that the preoperative Hyodo score of patients with postoperative respiratory complications was signi cantly higher than that of patients without postoperative respiratory complications [11]. This nding indicates that patients with postoperative respiratory complications tend to have severe preoperative dysphagia.…”
Section: Participants' Background Characteristicsmentioning
confidence: 83%
“…Participants in the oral-intake group were younger than those in the parenteral-intake group, and older age was a risk factor for dysphagia. A previous study reported that the preoperative Hyodo score of patients with postoperative respiratory complications was signi cantly higher than that of patients without postoperative respiratory complications [11]. This nding indicates that patients with postoperative respiratory complications tend to have severe preoperative dysphagia.…”
Section: Participants' Background Characteristicsmentioning
confidence: 83%
“…Individuals who undergo surgery for cervical spine disease with anterior or posterior access tend to develop oropharyngeal dysphagia, which is often severe during the first month and progressively diminishes in intensity over time [26]. Multivariable analyses have identified smoking status, prior cervical surgery, preoperative C2-C7 angle, preoperative dysphagia, preoperative chronic obstructive pulmonary disease, multilevel surgery, and intraoperative steroid use as significant risk factors for dysphagia after ACDF [26][27][28][29][30]. However, the prospective study by Opsenak et al failed to confirm these findings [31].…”
Section: Risk Factorsmentioning
confidence: 99%